Implementation and Evaluation of the Quranic Literacy Program at Madrasah Ibtidaiyah - St. Jumaeda; Sukri Tiaklow; Supriyanti Buton; Fajar Naqsyahbandi (Universitas Islam Negeri (UIN) Salatiga, 2026)
Objectives: This research aims to examine the implementation, evaluate the process, and evaluate the product of the Quranic literacy program at Madrasah Ibtidaiyah (Islamic primary school) in Ambon City, Indonesia. Method: This research employed a mixed-methods design. The sample consisted of 92 students from Grades V and VI across three Madrasah Ibtidaiyah in Ambon City, Indonesia. Data were collected through interviews, questionnaires, classroom observations, documentation, and performance-based tests. Qualitative data were analyzed using thematic analysis, while quantitative data were analyzed using paired-samples t-test, Cohen’s d effect size calculations, and multiple regression analysis. Results: The findings mapped key aspects of the implementation of the Quranic literacy program in Madrasah Ibtidaiyah in Ambon City, including objectives, activities, teaching methods, participants, infrastructure, student grouping, assessment, parental involvement, strengths, and challenges. Process evaluation indicated that the overall learning process was categorized as “Good”, with an average score of 3.87 on a 5-point scale. Product evaluation demonstrated that the Quranic literacy program had a statistically significant effect on student’ competency, resulting in an average competency score increase of 11.5 points. Theoretical Contribution: This research contributes to the development of Islamic education evaluation theory and extends Stufflebeam's CIPP evaluation model within the context of Quranic literacy programs. Implication: The findings offers a new framework for implementing and evaluating Quranic literacy programs in Islamic primary schools.